Peningkatan Kemampuan Menulis Puisi Melalui Quantum Learning Siswa Kelas VIII B SMP Negeri 3 Wawotobi - . Wawan (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to improve the ability to write poetry with Quantum Learning techniques in class VIII B Wawotobi 3 Public Middle School. 2017/2018 Academic Year. The method used in this research is descriptive quantitative. The place of this research is located in Wawotobi 3 Public Middle School. This research was conducted in class VIII B of Wawotobi 3 Public Middle School Academic Year 2017/2018, the subjects in this study were 16 people. The indicator of success in implementing this class action is that students achieve individual learning completeness when they have reached a minimum score of 67 and classical learning completeness is achieved when it has reached the value of 80% of students have achieved individual completeness. At the pretest activities the student learning outcomes were 946, with an average of 59.12, the first cycle increased to 1014, with an average value of 63.37, the second cycle increased to 1214, the average value was 76, and in the post-test scores students increased to 1369 with an average of 85. The percentage increase in learning activities of students in cycle I and cycle II can be seen from the increase in the percentage of the results of observation of student learning activities from the first cycle of 65% and increased in the second cycle by 90%. Information can be obtained that the number of students completing learning in the first cycle is 10 students, while in the second cycle there are 18 students. This shows that the difference in the increase in the number of students in cycle I and cycle II is 4 students or 50%. The number of students who did not complete in cycle I were 5 students and in cycle II there were 1 student. Student differences that did not complete between cycle I and cycle II were 4 students or 83.33%. The conclusion of this study is that the indicators of success in this study have been achieved, that is, at least 80% of students have reached 67. This means that the action hypothesis has been answered, namely by implementing the Quantum Learning learning model activities and learning outcomes of class VIII B SMP Negeri 3 Wawotobi can be improved.